2011
DOI: 10.3109/13693786.2010.539629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic-derived allyl sulphides on morphogenesis and hydrolytic enzyme secretion inCandida albicans

Abstract: The effect of diallyl sulphide (DAS) and diallyl disulphide (DADS) on secretion of hydrolytic enzymes and dimorphism has been investigated in two strains of Candida albicans. Minimum inhibitory concentration (MIC) of DADS and DAS was determined to be 500 μg/ml and 40 μg/ml, respectively for a clinical isolate (accession #3043) and 450 μg/ml and 50 μg/ml, respectively, for a reference strain (ATCC 90028). At one-half of the minimum inhibitory concentration (MIC), DAS and DADS inhibited proteinase secretion by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Proteinase assay was performed according to Yousuf et al [35]. Briefly, Candida strains were exposed to different concentrations of silver nanoparticles (MIC/8, MIC/4, MIC/2, and MIC) for 5 min.…”
Section: Proteinase Secretion Assaymentioning
confidence: 99%
“…Proteinase assay was performed according to Yousuf et al [35]. Briefly, Candida strains were exposed to different concentrations of silver nanoparticles (MIC/8, MIC/4, MIC/2, and MIC) for 5 min.…”
Section: Proteinase Secretion Assaymentioning
confidence: 99%
“…Candida parapsilosis ATCC 22019 was used as a negative control. Proteinase activity was determined by calculating the zone of digestion ( ) using the formula-ratio of the diameter of the colony to the sum of diameter of the colony and the zone (in mm) [13,14].…”
Section: Preparation Of the Inoculummentioning
confidence: 99%
“…For example, electron microscopic investigations revealed that addition of garlic can damage the cell membrane of Candida albicans and thereby inhibit the multiplication of this fungus (Lemar et al, 2002). Strong evidence in support of a reduction in the growth of Candida with garlic application was also provided by (Yousuf et al, 2011). Apart from Candida, many researchers have analyzed the effect of garlic on other fungi.…”
Section: Ef Icacy Of Garlic As An Anti-fungal Agentmentioning
confidence: 99%